1983
DOI: 10.1097/00000658-198302000-00018
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Prospective Study of 571 Patients Comparing Continuous vs. Interrupted Suture Techniques

Abstract: A randomized, prospective study was designed to compare a continuous with an interrupted technique for closing an abdominal incision. Five hundred seventy-one patients were randomized between the closure methods and stratified as to type of wound: clean, clean-contaminated, or contaminated. In mid-line incisions, the dehiscence rate was 2.0% (5/244) for the continuous group versus 0.9% (2/229) for the interrupted group. The difference was not statistically significant. Ventral hernias formed in 2.0% (4/201) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(76 citation statements)
references
References 10 publications
1
75
0
Order By: Relevance
“…The 17% reduction in abdominal closure time in our study achieved by closing the rectus sheath with a continuous suture is similar to the 18% found by Sahlin et al (30), but less than the 50 to 60% reported by others (18,20,25). These greater reductions in closure time may have been due to the larger incisions in some studies (18,20).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The 17% reduction in abdominal closure time in our study achieved by closing the rectus sheath with a continuous suture is similar to the 18% found by Sahlin et al (30), but less than the 50 to 60% reported by others (18,20,25). These greater reductions in closure time may have been due to the larger incisions in some studies (18,20).…”
Section: Discussionsupporting
confidence: 79%
“…The rate of abdominal wound dehiscence has been reported to range from 0 to 3.1% (8,15,22,25,30,31,39). Continuous closure is at least as safe as interrupted closure if correctly performed (1, 5,17,18,20,22,25,27,30,33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations